DISSOLUTION PROFILE STUDY OF EXTENDED RELEASE VALPROIC ACID DRUG PRODUCTS FROM DIFFERENT MANUFACTURERS - D. Yu. Grebenkin; E. D. Ustinova; S. Yu. Gorbacheva; A. K. Faeva; V. I. Kazey; A. V. Ryabova (Разработка и регистрация лекарственных средств)
Dissolution profiles of four extended release valproic acid tablets from different manufacturers and granules Depakine® Chronosphere 500 mg were studied in three dissolution media: pH 1.2; 4.5, 6.8 (quality control medium). Dissolution profiles similarity for tablets was approved and more rapid dissolution of Depakine® Chronosphere 500 mg was demonstrated in media pH 4.5, 6.8. API did slightly released in buffer pH 1.2 because of low solubility of valproate in acid form therefore these data were not taken into account.